Ekstrak Daun Asam Jawa (Tamarindus Indica L.) Sebagai Antidiabetes - Lahamado, Olfiana T.; Sabang, Sri Mulyani; Mustapa, Kasmudin (Jurnal Akademika Kimia, 2017)
One of the plant that is widely used as a medicinal plant is the leaves of tamarind (tamarindus indica L). This study aims to determine the effectiveness of anti-diabetic of tamarind (tamarindus indica L.) extract in lowering blood glucose levels in mice animals test. The experiment was performed using tamarind leaves extracted through infusion method. The animals test were 15 male mice induced by ethylene diamine tetra acetate (EDTA). Mice were divided randomly into 5 groups with different treatments. Treatments I, II and III were given tamarind leaves extracts for each with a concentration of 10%, 20% and 40%. Treatment IV was given glibenclamide suspense as a positive control (+), and the treatment V was given Na-CMC 1% as a negative control (-). Based on the analysis of variance statistical calculations tamarind leaves extracts can lower blood glucose levels on mice test. Furthermore, the significant difference was tested to check the concentration effect. The results on animals test with a significant level of 5% showed that the tamarind leaves extract of 40% or Treatment III affected on decreasing blood sugar levels on mice.